Description of the Process of Grieving and Depression in Patient with Coronary Hearth Disease in the Intensive Room - Dewi Dewi; Ayu Prawesti; Etika Emaliyawati (Universitas Padjadjaran, 2019)
Background: The process of grieving and depression can affect the treatment process and the condition of patients with coronary heart disease. The process experienced by the patient can be uncomplicated grief, complicated grief and depression. It is important to distinguish between uncomplicated grief, complicated grief and depression in response to normal and healthy loss and with response to the stresses of personal disorders that require more intensive intervention. The nurse is responsible for helping the patient go through the grieving process so as to prevent the adverse effects on the patient, so that the grieving and depression process are needed to determine the problems and to plan the nursing treatment.Objective: This study aimed to identify the process of grieving and depression in patients with coronary heart disease in the Intensive Room of Hospital Dr. Hasan Sadikin Bandung.Methods: This research method was quantitative descriptive. The study population of patients with coronary heart disease was an average of 37 people per month. Consecutive Sampling technique was carried out for one month with 34 respondents. Data collection technique used in this sresearch was the Grief / Depression Assessment Inventory questionnaire that had been tested for validity with the face validity and content validity. The collected data were analyzed by analytic descriptive method using frequency distribution.Result: The results showed that from 34 respondents, most of them (94.1%) had complicated grief while few of them (5.9%) had uncomplicated grief. The highest response to grieving and depression was in the domain of attitude, thought, feeling, and loss.Conclusion: Based on the results of the study, most patients with coronary heart experienced complicated grief. Therefore it was important for nurses to facilitate patients to be able to consult with treating doctors, psychologists, religious leaders or psychiatrists.Keywords: Coronary Heart Disease, Depression, Grieving